Medication, age and abstinence days associated with low semen quality: A cross-sectional study in more than 7000 men visiting the centre for reproductive medicine. - P G J Ter Horst; M A Edens; D den Besten-Bertholee; L W Mulder; M H J M Curfs (PLoS ONE)
Medication can affect semen quality by decreasing ejaculate volume, sperm concentration, or decreased sperm motility and sperm function in general. We performed a retrospective explorative cross-sectional study on any medication use and semen quality in our fertility clinic in men older than 18 years with a recorded semen analysis. Men were categorized based on medication use, i.e., any type, and no medication use. Exclusion criteria were incomplete semen analysis, azoospermia, a semen analysis after vasectomy, and days of abstinence less than 2 or more than 7 days before semen collection. The primary outcome was the composite endpoint of low semen quality (LSQ) according to the WHO. In total 722 men with medication and 6716 men without medication were included in the study. At the ATC-7 level (individual drug ATC-code), univariate (borderline) statistically significant associations using a cut-off of p < 0.100 were found for metformin (A10BA02), metoprolol (C07AB02) and lisinopril (C09AA03), which remained significant after adjustment for age and abstinence days. Our study is limited by the fact that information regarding exposure to information, as information was self-reported by patients. Also, the outcome, semen quality, was hindered by patients own collection. Even if a drug had logically been used for some time before semen sampling (e.g., medication for chronic disease), there was no way to determine whether that medication had been started before or after the occurrence of LSQ. Finally, medication and disease cannot be separated, hence it could not be determined whether the medication or the disease itself was associated with LSQ. Therefore, this study should be interpreted as a hypothesis-generating study.